2010
DOI: 10.1103/physrevb.81.245210
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiodescription of heterostructural alloys: Thermodynamic and structural properties ofMgxZn1xOandet al.

Abstract: Pseudobinary heterostructural alloys of ZnO with MgO or CdO are studied by composing the system locally of clusters with varying ratio of cations. We investigate fourfold (wurtzite structure) and sixfold (rocksalt structure) coordination of the atoms. By means of density functional theory we study a total number of 256 16-atom clusters divided into 22 classes for the wurtzite structure and 16 classes for the rocksalt structure for each of the alloy systems. The fraction with which each cluster contributes to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 62 publications
(112 reference statements)
3
43
1
Order By: Relevance
“…(1) and (2) [3,6,7,9,[23][24][25][26][27], which are consistent with our calculations. From the figures, we found that both bulk modulus and band gap of these alloys with rocksalt structure are larger than those with wurtzite structure.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…(1) and (2) [3,6,7,9,[23][24][25][26][27], which are consistent with our calculations. From the figures, we found that both bulk modulus and band gap of these alloys with rocksalt structure are larger than those with wurtzite structure.…”
Section: Resultssupporting
confidence: 93%
“…Alloying ZnO with other group-II metal oxides, the ternary alloys may possess band gap ranging continuously from about 2.3 to 10.6 eV through changing the dopant concentration. Much theoretical and experimental work has been carried out to investigate the ternary ZnObased alloys including Be x Zn 1Àx O, Mg x Zn 1Àx O, Ca x Zn 1Àx O and Cd x Zn 1Àx O [3][4][5][6][7][8], whose optoelectronic properties have been extensively studied. For Mg x Zn 1Àx O, Ca x Zn 1Àx O and Cd x Zn 1Àx O, the structure phase separation will occur in some transition concentration due to the large crystal structure mismatch between wurtzite ZnO and rocksalt MgO, CaO and CdO.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the point-group symmetry of wz, the total number of 2 n = 256 clusters is grouped into J + 1 = 22 classes. 40,43 A complete treatment of all classes of larger clusters, e. g. of 32-atom clusters with n = 16 would increase the CPU time too much because of the 2 n = 65 536 clusters needed to study. The 16-atom cell can be constructed in such a way that N atoms occupy the top and bottom surfaces of the cell (cf.…”
Section: A Cluster Expansion and Alloy Statisticsmentioning
confidence: 99%
“…(1) and (2) depend on the average composition x of the alloy as well as the temperature T , hence, it is possible to account for the influence of different preparation conditions. 43 In this work, three situations are distinguished:…”
Section: B Configurational Averagementioning
confidence: 99%
See 1 more Smart Citation